1980
DOI: 10.1080/00365518009091979
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of bone mineral content (BMC) of the lumbar spine, II. Correlation between forearm BMC and lumbar spine BMC

Abstract: A comparison between forearm bone mineral content (BMC) and lumbar BMC was made in post-menopausal women. Women without symptoms, women with clinical spinal osteoporosis, and women with prednisone-treated rheumatoid arthritis were studied. A conventional two-dimensional single-photon osteodensitometer was used for measurement of forearm BMC. A new two-dimensional dual-photon osteodensitometer was used for measurement of lumbar BMC. Its radioactive source was 153Gadolinium. The mean lumbar BMC was significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1986
1986
1994
1994

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Although the radial density was moderately correlated with spinal density in both patients and normal subjects, the prediction error was too large (>25% at the 95% confidence interval) to allow even gross quantitative assessment of the spine. Previous studies have reported similar findings (6)(7)(8)(9)22,23). Conceivably, appendicular sites containing more trabecular bone could be expected to give better prediction, but this is not the case.…”
Section: Discussionmentioning
confidence: 55%
“…Although the radial density was moderately correlated with spinal density in both patients and normal subjects, the prediction error was too large (>25% at the 95% confidence interval) to allow even gross quantitative assessment of the spine. Previous studies have reported similar findings (6)(7)(8)(9)22,23). Conceivably, appendicular sites containing more trabecular bone could be expected to give better prediction, but this is not the case.…”
Section: Discussionmentioning
confidence: 55%
“…Bone mineral measurements in healthy (human) individuals have shown that there is not a significant difference between bone mineral in the left and the right leg, when identical sites of measurement in the lower extremities are compared (9,10). For more than the past decade dual photon absorptiometry (DPA) has been used to measure bone mineral content (BMC) and bone mineral density (BMD) at various measuring sites throughout the human skeleton (7,(11)(12)(13). In contrast to other methods to estimate bone mineral in vitro, the method using DPA is non-invasive, with a high accuracy and a precision error between 2-3% (14).…”
mentioning
confidence: 99%